DESKRIPSI KINERJA PRODUK WIRAUSAHA WANITA DALAM MENDUKUNG SDGS & ASTA CITA - Sulung Rahmawan Wira Ghani; Syai'in; Agus Sulthon; Kusnul Ciptanila Yuni K (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The  role  of  female  entrepreneurs  in  the  business  world  is  increasingly  growing,  no  longer  dominated  by  men,  but  also  by  women  who  are  now  actively  participating  as  business  owners.  The  main  characteristic  of  female  entrepreneurs  is  their  ability  to  manage  time  flexibly,  especially  for  those  who  are  married,  allowing  them  to  run  a  business  while  taking  care  of  their  families.  Factors  that  encourage  women  to  become  entrepreneurs  include  emancipation,  higher  education,  the  desire  to  support  family  economics,  and  opportunities  for  personal  development.  The  presence  of  female  entrepreneurs  also  contributes  to  the  achievement  of  the  Sustainable  Development  Goals  (SDGs),  such  as  poverty  eradication  (Goal  1),  gender  equality  (Goal  5),  decent  work  and  economic  growth  (Goal  8),  and  reduced  inequalities  (Goal  10).  Furthermore,  with  the  growing  interest  in  religious  tourism,  female  entrepreneurs  play  a  crucial  role  in  supporting  the  economic  movement  in  this  sector  while  also  contributing  to  the  realization  of  Asta  Cita,  the  noble  ideals  of  creating  shared  prosperity.  This  study  aims  to  explore  the  role  of  female  entrepreneurs  in  the  religious  tourism  industry  area  of  Tebuireng,  particularly  in  relation  to  the  SDGs  and  Asta  Cita,  and  their  contribution  to  more  inclusive  and  sustainable  economic  and  social  development.  The  results  of  this  study  show  that  the  contribution  of  products  offered  by  women  entrepreneurs  in  the  religious  tourism  area  is  as  follows:  Cluster  1  contains  the  same  products,  accounting  for  48%  (48  sample  data),  Cluster  2  contains  the  same  products,  accounting  for  11%  (6  sample  data),  Cluster  3  contains  the  same  products,  accounting  for  35%  (19  sample  data),  and  Cluster  4  contains  the  same  products,  accounting  for  6%.